Manajemen Kurikulum Pendidikan Agama Islam bagi Anak Berkebutuhan Khusus di SLB Al Azhar Bukittinggi - Sri Intan Wahyuni (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this research is to analyse the implementation of the curriculum management of Islamic education subject for students with special needs in SLB Al Azhar , Bukittinggi. This research used qualitative approach. The data was collected through observation and interview with Islamic education teachers, the curriculum vice principal for curriculum affairs and the head master of the school. The result showed that 1) The curriculum is designed by the vice principal for curriculum affairs and the Islamic education teachers by providing syllabus and daily instructional plan appropriate for all types of disabilities in SLB Al Azhar Bukittinggi. 2) the curriculum is implemented by teacher in instructional process by adjusting the material with the lowest types of disabilities in the class, 3) the assessment is conducted through teaching-learning evaluation and assignment given to students with disabilities. However, some teachers still have difficulties in teaching due to the lack of educational background related to special education.